HUBUNGAN KECEPATAN LARI DAN KELINCAHAN TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SISWA PUTRA YANG MENGIKUTI EKSTRAKURIKULER BOLA BASKET SMA NEGERI 3 MANDAU - PUTRA, SEFTIA KELANA; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study was conducted with the aim of finding out more about therelationship between running speed and agility towards the results of dribbling skills inmale students who took extra-curricular basketball at SMA Negeri 3 Mandau. Theproblem found in this study is that in SMA Negeri 3 Mandau, each match has not beenoptimal in the way of dribbling the basketball as a result, the opponent easily seizes theball from the team. This research was conducted in the field of SMA Negeri 3 Mandau,which is located at JL. Tuanku Tambusai 24 Duri. Held from March to July. The pupilsin this study were male students of basketball extracurricular activities at SMA Negeri 3Mandau. While the sampling technique used is a sample study, which uses a portion ofthe population. Based on the research results, the following partial conclusions can bedrawn: there is a low relationship between running speed and the results of dribblingskills where r table at the significant rate is α = 0, (05) = 0.602 means rcount (0.313)>rtabel (0.602), there are There is a strong relationship between agility and the results ofdribbling where rtabel at the rate is significant α = 0, (05) = 0.602 means rcount(0.606)> rtabel (0.602), there is a very strong relationship together with therelationship between running speed and agility towards skills dribbling the ball formale students who take basketball extracurriculars at SMA Negeri 3 Mandau wherertabel at the rate is significant α = 0, (05) = 0.602 means rcount (0.1573)> r table(0.602).Key Words: Running Speed, Agility, Dribbling